High-resolution Arduino-based data acquisition devices for microscale separation systems - Itterheimová, Petra; Foret, František; Kubáň, Petr (Analytica chimica acta, 2021)
In this work, we have designed, constructed, and evaluated simple, inexpensive open-source data acquisition systems based on various analog-to-digital converter modules (ADS 1115, MCP 3424, LTC 2400, with resolution from 16 to 24-bit) and a miniature Arduino Nano ™ microcontroller. The constructed data acquisition systems provide excellent performance and are comparable to a commercial, 24-bit device. We provide full schematics and corresponding source codes so that analytical chemists can easily construct any of the developed systems without extensive electronic or programming knowledge. The 24-bit LTC 2400 based device provided the best and comparable performance to a commercial, high-end 24-bit sigma to delta converter (ORCA 2800) at a fraction of cost (less than 50 USD compared to 870 USD for the commercial counterpart). The excellent performance was verified using a capillary electrophoresis system with contactless conductivity detection and separation of inorganic ions in clinical skin wipe and tap water samples.
Keywords: elektroforéza kapilární; Software; software; Capillary electrophoresis; Open source hardware and software; Water; Microscale separations; Ions; ionty; Arduino; Electric Conductivity; elektrická vodivost; voda; Data acquisition; Electrophoresis, Capillary